Style and lanquage videomaking (Herald of Journalism, 2018)
The article examine the importance of creating special effects and computer video editing. Also as the creation of the video – the releationship between partners. To make TV programs are creative work. Theoretically hand-writing the script, prepare texts, decorate the melody – is concept of the products. The Advantage of the fact that today the industrial-innovative development has proved to be a new way of world competition act and science. On this side to make TV programs. TV shows, TV movies are cognitive improvement. Specialists who are partici parting in the process, set a goal that exolic quality of TV programs rouse on the global level. TV project activity of Euro Median culture, creative ability, free technology tendency progressively expand science and knowledge gave conceptiative solutions. Including methods of TV design talks about the importance of convergent journalist.Key words: computer video editing, offscreen text, innovation development at technology, editor, programmer, special effects.
Keywords: Key words: computer video editing, offscreen text, innovation development at technology, editor, programmer, special effects.